Pharmacologic and Regenerative Cell Therapy for Spinal Cord Injury: WFNS Spine Committee Recommendations - Toshihiro Takami; Nobuyuki Shimokawa; Jutty Parthiban; Mehmet Zileli; Sheena Ali (Neurospine, 2020)
This is a review article examining the pharmacologic and regenerative cell therapy for spinal cord injury. A literature search during last 10 years were conducted using key words. Case reports, experimental (nonhuman) studies, papers other than English language were excluded. Up-to-date information on the pharmacologic and regenerative cell therapy for spinal cord injury was reviewed and statements were produced to reach a consensus in 2 separate consensus meeting of WFNS Spine Committee. The statements were voted and reached a consensus using Delphi method. Pharmacologic and regenerative cell therapy for spinal cord injury have long been an interest of many experimental and clinical researches. Clinical studies with methylpredinisolone have not shown clear cut benefit. Other drugs such as Rho inhibitor, minocycline, riluzole, granulocyte colony-stimulating factor have also been tried without significant benefits. Regenerative cell therapy using different types of stem cells, different inoculation techniques, and scaffolds have undergone many trials highlighting the efficacies of cells and their limitations. This review article summarizes the current knowledge on pharmacologic and regenerative cell therapy for spinal cord injury. Unfortunately, there is a need for further experimental and human trials to recommend effective pharmacologic and regenerative cell therapy.